2009
DOI: 10.3928/01484834-20091113-06
|View full text |Cite
|
Sign up to set email alerts
|

Developing Patient-Centered Care Competencies Among Prelicensure Nursing Students Using Simulation

Abstract: Health care improvement requires collaboration between academia and practice to bridge gaps in nurse education and achievement of quality outcomes. Quality and Safety Education for Nurses identified six domains, including patient-centered care, that should be addressed during prelicensure education. Simulation is a recommended strategy to teach safe clinical practice; however, cost, space, and faculty resources are barriers to its use. Computer-based social simulation is less resource intensive and effective i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 15 publications
1
22
0
Order By: Relevance
“…Our safety competency results show a high (r=0.65–0.80)35 45 55 or modest (r=0.34)56 correlation with technical skills. Conversely, they exhibit a low (r=0.13)32 68 or modest (r=0.25)32 35 68 correlation with final written examination scores. Performance scores were also compared across training levels and trainee characteristics for 13 of our assessment tools (38%); 11 tools in 17 studies produced scores that increased with training level,23–26 33 37–39 45 48 49 52 57–59 61 67 while for three tools in four studies this trend was not observed 36 41 53 62.…”
Section: Resultsmentioning
confidence: 94%
“…Our safety competency results show a high (r=0.65–0.80)35 45 55 or modest (r=0.34)56 correlation with technical skills. Conversely, they exhibit a low (r=0.13)32 68 or modest (r=0.25)32 35 68 correlation with final written examination scores. Performance scores were also compared across training levels and trainee characteristics for 13 of our assessment tools (38%); 11 tools in 17 studies produced scores that increased with training level,23–26 33 37–39 45 48 49 52 57–59 61 67 while for three tools in four studies this trend was not observed 36 41 53 62.…”
Section: Resultsmentioning
confidence: 94%
“…At the same time, simulated education solutions have shown no significant difference in either learning outcomes or student satisfaction when compared with other simulation modalities (5). Yet, the use of virtual patient simulations has particular unique benefits that include the asynchronous, computer-based delivery of clinical situations, which eliminates the necessity for patient actor recruitment and training (7); the complete standardization of the patient encounter, which removes any possible subjectivity that may exist in simulations conducted with a human patient actor (8); and the transparency into student performance provided to instructors through verbatim transcripts of each interaction (9). …”
mentioning
confidence: 99%
“…The current literature contains many examples of how simulated clinical activities can assist in the development of critical thinking ability, largely due to the guided debriefing that follows the simulated scenario [21,22] . The need for intensive faculty training and costs has been identified as barriers.…”
Section: Simulationmentioning
confidence: 99%
“…The use of simulation with high-fidelity mannequins has shown to be an effective teaching strategy for nursing students [19][20][21][22] .…”
Section: Critical Thinking Interventionsmentioning
confidence: 99%